2002
DOI: 10.1046/j.1365-2591.2002.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of endodontic practice amongst Flemish dentists

Abstract: The results of this study confirm that many Flemish general practitioners are not following quality guidelines for endodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
137
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(163 citation statements)
references
References 22 publications
18
137
2
6
Order By: Relevance
“…Most of the GDPs (86%) never used rubber dam which was similar among those of Hong Kong,Belgium and Sudan. 2,4,6 This may be due to cost, skill and time factors and may influence the choice of irrigant and negatively affect treatment outcome. 8 Rubber dam application for endodontic treatment is mandatory for patient protection and isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the GDPs (86%) never used rubber dam which was similar among those of Hong Kong,Belgium and Sudan. 2,4,6 This may be due to cost, skill and time factors and may influence the choice of irrigant and negatively affect treatment outcome. 8 Rubber dam application for endodontic treatment is mandatory for patient protection and isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous questionnaire surveys done in developed and developing countries like United Kingdom (UK), Hong Kong (HK), North Jordan, Belgium, India and Sudan has shown that the most general dental practitioners (GDPs) and endodontists practice what they have been taught in their dental school and fail to apply new technologies and materials in their daily practice, while others practiced the technologies with no scientific basis. [1][2][3][4][5][6] There are no study done in this field in Nepal and hence it is a necessity to conduct such survey to gain knowledge regarding endodontic practice profile, implementation of new technologies and identify the problems in implementation of these methods and materials and need for organization of further endodontic continued dental education programs.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Although surveys reported that almost all undergraduate students expected to use the RD in endodontics post-qualification, 3,19 RD use tends to decrease dramatically after graduation ( Table 1). The number of years of professional activity after graduation may not contribute significantly to the attitude of the GDPs towards the application of RD.…”
Section: Prevalence Of Rubber Dam Usementioning
confidence: 99%
“…Undergraduate curriculum guidelines have been formulated by the American Dental Association to define the acceptable standard of care in clinical endodontics [1]. Several studies, however, have reported that the majority of dentists are h these guidelines [2][3][4]. the attitude of dentists in Western 7].…”
Section: Introductionmentioning
confidence: 99%